2014
DOI: 10.1117/1.jbo.19.5.057011
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer detection by time-resolved spectra of blood components

Abstract: Abstract. Fluorescence spectral techniques are very sensitive, and hence they are gaining importance in cancer detection. The biomarkers indicative of cancer could be identified and quantified by spectral or time domain fluorescence spectroscopy. The results of an investigation of time-resolved spectra of cellular components of blood obtained from cervical cancer patients and normal controls are given. The cancer indicative biomarker in this paper is porphyrin; it has a fluorescence decay time of 60% more in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 17 publications
(31 reference statements)
3
11
0
Order By: Relevance
“…These values are less for the control group but at their maximum for cancer patients. Normal porphyrin was elevated for the patients, consistent with previous results (see Table 4 ) ( Kalaivani et al, 2014 ). Weber and co-workers (2013) use the methods of fluorescence spectroscopy to examine and measure the uptake of DOX chemotherapeutic drug in human breast cancer cells.…”
Section: Discussionsupporting
confidence: 92%
“…These values are less for the control group but at their maximum for cancer patients. Normal porphyrin was elevated for the patients, consistent with previous results (see Table 4 ) ( Kalaivani et al, 2014 ). Weber and co-workers (2013) use the methods of fluorescence spectroscopy to examine and measure the uptake of DOX chemotherapeutic drug in human breast cancer cells.…”
Section: Discussionsupporting
confidence: 92%
“…Masilamani et al observed enhanced fluorescence bands (one around 590 nm and another around 630 nm) in blood samples for several different types of cancers, such as gastric cancer, breast cancer, and Hodgkin's lymphoma [40]. Kalaivani et al found elevated porphyrin fluorescence in the blood components of cervical cancer patients [36]. It indicates that porphyrins accumulate more in tumor parts.…”
Section: Discussionmentioning
confidence: 97%
“…The spectra were normalized to 100% at the peak maximum and then calculated with curve-fitting. The wide spectra were contributed by several endogenous fluorophores, such as free NADH, protein-bound NADH, free FAD, basic form, and neutral form of porphyrins [36], tryptophan, collagen, and elastin. The fluorescence of protein-bound FAD is very weak [37] and not considered in this study.…”
Section: Autofluorescence Spectra Of Lung Tissue Samplesmentioning
confidence: 99%
“…There has been some reports using native fluorescence spectroscopy for cervical cancer detection on blood samples [26,27], urine samples [27], animal models [28], cell lines [29,30], human cervical tissue sections [24,31,32] and in vivo by colposcopy [33]. Most of the studies reported the intensity difference between healthy and cancerous samples, but the sensitivities in the literature are variable, ranging from 62% to 92% [26,33].…”
mentioning
confidence: 99%